Gut mobilization improves behavioral symptoms and modulates urinary p‐cresol in chronically constipated autistic children: A prospective study. Issue 1 (23rd November 2021) - Turriziani, Laura; Ricciardello, Arianna; Cucinotta, Francesca; Bellomo, Fabiana; Turturo, Giada; Boncoddo, Maria; Mirabelli, Silvestro; Scattoni, Maria Luisa; Rossi, Maddalena; Persico, Antonio M.
Abstract: Chronic constipation is common among children with ASD and is associated with more severe hyperactivity, anxiety, irritability, and repetitive behaviors. Young autistic children with chronic constipation display higher urinary, and foecal concentrations of p‐cresol, an aromatic compound produced by gut bacteria, known to negatively affect brain function. Acute p‐cresol administration to BTBR mice enhances anxiety, hyperactivity and stereotypic behaviors, while blunting social interaction. This study was undertaken to prospectively assess the behavioral effects of gut mobilization in young autistic children with chronic constipation, and to verify their possible correlation with urinary p‐cresol. To this aim, 21 chronically constipated autistic children 2–8 years old were evaluated before (T0), 1 month (T1), and 6 months (T2) after intestinal mobilization, recording Bristol stool scale scores, urinary p‐cresol concentrations, and behavioral scores for social interaction deficits, stereotypic behaviors, anxiety, and hyperactivity. Gut mobilization yielded a progressive and highly significant decrease in all behavioral symptoms over the 6‐month study period. Urinary p‐cresol levels displayed variable trends not significantly correlated with changes in behavioral parameters, mainly increasing at T1 and decreasing at T2. These results support gut mobilization as a simple strategy to ameliorate ASD symptoms, as well as comorbid anxiety and hyperactivity, in chronically constipated children. Variation in p‐cresol absorption seemingly provides limited contributions, if any, to these behavioral changes. Further research will be needed to address the relative role of reduced abdominal discomfort following mobilization, as compared to specific modifications in microbiome composition and in gut bacteria‐derived neuroactive compounds. Lay Summary: Many autistic children suffer from chronic constipation. Gut mobilization in 21 chronically constipated autistic children followed prospectively for 6 months, consistently reduced hyperactivity, anxiety, sociocommunication deficits, restricted interests, and stereotypic behaviors. Changes in urinary p‐cresol, a gut bacteria‐derived neuroactive compound able to negatively affect brain function in rodent models, was not correlated with behavioral parameters, except for a marginal association with changes in anxiety. Gut mobilization significantly improves behavioral symptoms in chronically constipated autistic children, through multiple mechanisms possibly including, but not limited to, reduction in p‐cresol absorption.